Humanity in Public Service Advertisement “Sayyidi al Raīs” by Zain Group: Critical Discourse Analysis - Nurul Ulmi Mansur (Universitas Islam Negeri Sunan Kalijaga, 2020)
In reality of life, humanitarian crises occur everywhere, including in the Middle East. The superpowers that have a special role in the world order seem to have closed their eyes to this case. Prolonged war, national, everywhere, and authoritarian rulers make peace even farther from the word. Advertisement is a medium to introduce and disseminate something. Recently, public service announcements have appeared that aim to reach or resolve issues that occur in society. This is what encourages the author to connect the micro text in advertisement itself with the macro text or reality in society, so the purpose of this research is to reveal attitudes and views in an advertisement in a humanitarian situation. The research data is in the form of fragments of song lyrics and pictures shown in Sayyidi al Rai>s advertisements. The data analysis was conducted descriptively-critical with analysis of the Fairclough critical discourse approach to explain the meaning of linguistic components such as vocabulary, modality, and grammar, so as to be able to reconstruct the discourse in the advertisement. Based on the results of the author's analysis, that a text is not static but a text has a relationship between one text and another or in society’s life. The result of this study concluded that Zain Group advertised or stated, in humanity, nationality and isolation were still rife in the world. It has a dialectical relationship with events that occur in society such as differences in the ideology of the superpowers with other countries, especially in Middle Eastern countries.